2011
DOI: 10.1155/2011/590356
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Quality in Lower Gastrointestinal Endoscopy from the Patient Perspective

Abstract: Factors related to comfort, staff, communication and the service environment were evaluated from the patient perspective using closed-ended questions that were designed by clinicians and researchers. Future research using qualitative methodology to elicit the patient perspective on quality in colonoscopy and⁄or endoscopy services is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…• The results of endoscopic procedures should be communicated in a timely manner, both to the patient and to the referring physician Timely communication of results is frequently rated highly in patient surveys (35); however, patients often leave endoscopy units without knowing when they will receive their results or without clear discharge and follow-up plans (10). It is the endoscopist's responsibility to ensure that results are communicated to the patient.…”
Section: Communicating Resultsmentioning
confidence: 99%
“…• The results of endoscopic procedures should be communicated in a timely manner, both to the patient and to the referring physician Timely communication of results is frequently rated highly in patient surveys (35); however, patients often leave endoscopy units without knowing when they will receive their results or without clear discharge and follow-up plans (10). It is the endoscopist's responsibility to ensure that results are communicated to the patient.…”
Section: Communicating Resultsmentioning
confidence: 99%
“…This may be a consequence of factors unrelated to the technical performance of colonoscopy such as good communication, explanation and short waiting times, which are known to influence these outcomes [23]. This may be a consequence of factors unrelated to the technical performance of colonoscopy such as good communication, explanation and short waiting times, which are known to influence these outcomes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with favorable endoscopy experience are more likely to comply with medical advice, adhere to screening and use medical service in the future, whereas patients with poor experience are more likely to leave their care provider and be less compliant [19] . A systematic review of literature showed that the control of discomfort and pain during the colonoscopy was considered to be a high priority by patients [20] . Given the mind's ability to influence the pain perceived during colonoscopy, acting on the pain and/or patient's discomfort is mandatory to break the trinomial "colonoscopy, pain and fears".…”
Section: Relationship Among Pain Fear and Anxietymentioning
confidence: 99%